AI LITERACY COMPETENCIES FOR TEACHERS: A BIBLIOMETRIC ANALYSIS OF SCOPUS-INDEXED PUBLICATIONS FROM 2020 TO 2025 - Indah Khoerunnisa (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
ABSTRACT The rapid development of artificial intelligence (AI), particularly generative artificial intelligence, has transformed educational practices and created new demands for teachers to possess AI literacy competencies encompassing conceptual understanding, pedagogical capabilities, critical evaluation, and ethical awareness. Although research on teachers’ AI literacy has grown substantially, comprehensive mapping of publication trends, intellectual structures, dominant themes, and future research directions remains limited. This study aims to analyze the development of research on teachers’ AI literacy competencies through a bibliometric approach. The dataset consisted of 625 Scopus-indexed documents published between 2020 and 2025. Data were analyzed using Biblioshiny in the R-bibliometrix package and VOSviewer through publication productivity analysis, journal source analysis, geographic distribution mapping, co-citation analysis, keyword co-occurrence analysis, and thematic mapping. The findings reveal a remarkable increase in publications, with an annual growth rate of 239.65%, particularly during 2024 and 2025. Knowledge production in this field is dominated by countries and institutions from East Asia, especially China and Hong Kong. Major research themes include AI literacy competency frameworks, the integration of generative AI in teacher education, assessment instrument development, and AI ethics. The study also identifies several research gaps, including the limited representation of Global South contexts, the scarcity of longitudinal studies, the lack of validated AI ethics instruments, and the limited adoption of teacher-involved co-design approaches. These findings provide a conceptual and empirical foundation for developing adaptive, contextualized, and ethically oriented teacher education and professional development programs in the AI era. ABSTRAK Perkembangan kecerdasan buatan (artificial intelligence/AI), khususnya generative artificial intelligence, telah mengubah lanskap pendidikan dan menuntut guru memiliki kompetensi literasi AI yang mencakup pemahaman konseptual, kemampuan pedagogis, evaluasi kritis, serta kesadaran etis dalam pemanfaatannya. Meskipun kajian mengenai literasi AI guru terus berkembang, pemetaan komprehensif mengenai tren publikasi, struktur intelektual, tema penelitian dominan, dan arah pengembangan riset masih terbatas. Penelitian ini bertujuan untuk menganalisis perkembangan penelitian kompetensi literasi AI guru melalui pendekatan bibliometrik. Data penelitian berasal dari 625 dokumen terindeks Scopus yang diterbitkan pada periode 2020–2025. Analisis dilakukan menggunakan Biblioshiny dalam paket R-bibliometrix dan VOSviewer melalui analisis produktivitas publikasi, sumber jurnal, distribusi geografis, ko-sitasi, ko-kata kunci, serta peta tematik. Hasil penelitian menunjukkan bahwa publikasi mengalami peningkatan yang sangat signifikan dengan annual growth rate sebesar 239,65%, terutama pada tahun 2024 dan 2025. Produksi pengetahuan didominasi oleh negara dan institusi di kawasan Asia Timur, khususnya Tiongkok dan Hong Kong. Tema penelitian yang berkembang meliputi kerangka kompetensi literasi AI, integrasi generative AI dalam pendidikan guru, pengembangan instrumen asesmen, serta etika penggunaan AI. Selain itu, penelitian ini mengidentifikasi beberapa celah riset, yaitu terbatasnya kajian di kawasan Global South, minimnya studi longitudinal, kurangnya instrumen etika AI yang tervalidasi, dan rendahnya penerapan pendekatan co-design yang melibatkan guru. Temuan ini memberikan dasar konseptual dan empiris bagi pengembangan program pendidikan dan pelatihan guru yang adaptif, kontekstual, serta berorientasi pada penggunaan AI yang etis dan berkelanjutan.